MacMahon's conjecture on symmetric plane partitions - Andrews, George E. (1977)
In 1898, P. A. MacMahon conjectured that the generating function for symmetric plane partitions with at most s rows and each part at most j has an especially simple closed form. An outline of the proof of this conjecture is given here.